2014
DOI: 10.1515/jcim-2012-0057
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemic effect of Rhizophora mucronata in streptozotocin induced diabetic rats

Abstract: Rhizophora mucronata, plant of Mangroove family, found on the coastal region of India and used in treatment of various diseases. Different parts of plants are used in treatment of diabetes as folkloric medicine. The present study was designed to evaluate the hypoglycemic effect of hydro-alcoholic extract of R. mucronata. Streptozotocin (STZ)-induced diabetic rats were treated with RME (100 mg/kg and 200 mg/kg) and glibenclamide (0.5 mg/kg). Blood glucose levels were evaluated for the acute and sub-acute studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…The similar result was reported for Rhizophora mucornata in which high dose (200mg/kg) of hydroalcoholic extract of the plant was found more potent than the low dose in first 6 h of the study. 16 For the daily treatment of SOE and glibenclamide up to 28days, it was found that the higher dose of SOE (51.21%) was more significant than SOE low dose (38.98%) in blood glucose lowering while compared to glibenclamide (55.97%). The similar study of the hypoglycemic effect of Kyllinga triceps plant extracts at 200mg/kg on STZ induced rats was reported as a significant (47.2% blood glucose reduction) than low dose.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The similar result was reported for Rhizophora mucornata in which high dose (200mg/kg) of hydroalcoholic extract of the plant was found more potent than the low dose in first 6 h of the study. 16 For the daily treatment of SOE and glibenclamide up to 28days, it was found that the higher dose of SOE (51.21%) was more significant than SOE low dose (38.98%) in blood glucose lowering while compared to glibenclamide (55.97%). The similar study of the hypoglycemic effect of Kyllinga triceps plant extracts at 200mg/kg on STZ induced rats was reported as a significant (47.2% blood glucose reduction) than low dose.…”
Section: Discussionmentioning
confidence: 96%
“…The blood samples were collected from all the rats through tail-vein and blood glucose levels were measured (in mg/dL) instantly by using glucometer (Accu-chek, Roche Diagnostic, Mannheim, Germany). 16…”
Section: Blood Glucose Estimationmentioning
confidence: 99%
“…19 Some recent studies also supported that hydro-alcoholic extract of R. mucronata leaves exhibited antiradical and anti-diabetic effects. 12,13 A study from Bangladesh demonstrated that, the ethanol extracts of Rhizophora mucronata Poir leaves showed significant inhibition of carbohydrate digestion and absorption, which has resulted in hypoglycemic effects of Rhizophora mucronata.…”
Section: Discussionmentioning
confidence: 99%
“…5 In South Asian countries together with India, the leaves of R. mucronata are being used traditionally for the remedy of diabetes. 6,7 It is abundantly found on the coastal region. R. mucronata L. leaves showed the presence of a good amount of polyphenols, like flavonoid, tannin, glycoside, phenolic compounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation